2019
DOI: 10.1097/01.hs9.0000564348.52740.18
|View full text |Cite
|
Sign up to set email alerts
|

Ps1522 Central Physiologic Mechanisms Which Augment Oxygen Release (Bohr Effect and 2,3‐dpg Binding) Are Preserved in the Presence of Voxelotor at the Therapeutic Target of 30% Hb Modification

Abstract: Background: Amongst patients with sickle cell disease (SCD) the leading cause of death is the acute chest syndrome (ACS). This pneumonia-like complication frequently occurs during or shortly after a vaso-occlusive crisis (VOC). In pediatric patients hospitalized for VOC, incentive spirometry has demonstrated to prevent the development of ACS. Aims: This study was designed to determine if a comparable effect of incentive spirometry can be demonstrated in adult patients with SCD. Furthermore, we aimed to validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…To determine the physiological relevance of a small rise in EPO (with no change in Hb concentration) on the oxygen affinity of Hb, the effects of voxelotor on other important regulators of Hb affinity (e.g., 2,3-diphosphoglycerate concentration) should be explored in vivo. In vitro, however, voxelotor does not inhibit the Bohr effect or offloading effects of 2,3-DPG (32). Given the complex biochemical regulation of Hb and the numerous physiological determinants of oxygen transport -which are each both individually and collectively modulated by hypoxia -additional integrative physiology studies are warranted to determine the potential clinical and physiological utility of allosteric Hb modulators.…”
Section: On Day 15)mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the physiological relevance of a small rise in EPO (with no change in Hb concentration) on the oxygen affinity of Hb, the effects of voxelotor on other important regulators of Hb affinity (e.g., 2,3-diphosphoglycerate concentration) should be explored in vivo. In vitro, however, voxelotor does not inhibit the Bohr effect or offloading effects of 2,3-DPG (32). Given the complex biochemical regulation of Hb and the numerous physiological determinants of oxygen transport -which are each both individually and collectively modulated by hypoxia -additional integrative physiology studies are warranted to determine the potential clinical and physiological utility of allosteric Hb modulators.…”
Section: On Day 15)mentioning
confidence: 99%
“…This effect is reversible and dose-dependent (29,33) as measured by the percent occupancy of Hb (22,27). Interestingly, in experimental models voxelotor-modified Hb retains the Bohr effect (i.e., releases more oxygen with increasing acidity) and responds to allosteric modulators such as 2,3-diphosphoglycerate, albeit with a mildly reduced rate of oxygen unloading (32). In animal studies under hypoxic conditions, ~30% drug occupancy of Hb has been shown to increase the overall affinity for oxygen in the blood, as evidenced by increased arterial oxygen saturation, with associated reduction in tissue hypoxia and improved survival (10).…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, voxelotor-modified hemoglobin was shown to still respond to the natural right-shifting substances (promoting oxygen offloading) concentrated in metabolically active tissue: H + and 2,3-DPG. 59 Some have expressed concern, though, that even slightly decreased oxygen offloading in the brain would, via normally functioning metabolic sensors in the brain, increase cerebral blood flow, which in the presence of chronic cerebrovascular disease could again result in stroke. Even in wild-type mouse models with presumed normal baseline p50 (i.e.…”
Section: Preclinical Resultsmentioning
confidence: 99%
“…For example, voxelotor binds allosterically to some, but not all hemoglobin and increases Hb-O 2 affinity. Hemoglobin modified with voxelotor exhibits a reduced Bohr effect compared to unmodified hemoglobin (Pochron et al, 2019), which may limit O 2 offloading during instances where blood pH decreases such as rigorous exercise.…”
Section: Pharmacological Induction Of High Hemoglobin-oxygen Affinitymentioning
confidence: 99%
“…Recently, Stewart et al (2021) showed that pharmaceutical induction of high Hb-O 2 affinity (only ∼2 mmHg decrease in P 50 ) using voxelotor reduced normoxic maximal O 2 consumption ( VO 2max ) in humans. The decrement in normoxic VO 2max observed by Stewart et al (2021) could be due to both an increase in Hb-O 2 affinity and a reduced Bohr effect: the transient reduction of Hb-O 2 affinity with decreasing pH (Pochron et al, 2019). A reduced Bohr effect in exercising muscle would further compromise O 2 off-loading, particularly during periods of high metabolic demand (Mairbäurl, 2013).…”
Section: High Hemoglobin-oxygen Affinity and Cardiorespiratory Adjust...mentioning
confidence: 99%